The Artefacts of News of Rubbish Dumps, Plays, Work, and “the First Draft of History” - Palmer, Michael (Javnost-The Public, 2003)
News is a contraction of two words : "new things". And news is the report of those "new things." These reports over time can themselves become artefacts. Historians, anthropologists, sociologists -along with journalists-study news. In different ways and via a range of media, dramatists, paleo-anthropologists and poets also pinpoint-sometimes en passant-the production, transmission and impact of news. Here we look at the seemingly unlikely "cross-fertilisation" of these remarks, and pick up points made by newsmen working at speed to capture "a defining moment," a story and its impact.